Clinical Profile of Spontaneously Regressed Retinoblastoma Tumours - Al-Mesfer, Saleh S; Souru, Ches; Khandekar, Rajiv (Archives of Clinical and Medical Case Reports, 2020)
Retinoblastoma is leading ocular malignancy in children. Newer modalities of treatment have improved the survival and eye preservation rate. However, very few reported cases document spontaneous regression of tumour in eye without any treatment. The paediatric ophthalmology and ocular oncology unit of our tertiary eye institute had noted three cases between 1983 and 2015. We present clinical features at presentation and progress noted during follow up. Histopathologic confirmation of diagnosis in such cases is not possible. However, clinical diagnosis by expert in the field in these cases is reliable.